Advances in mt-tRNA Mutation-Caused Mitochondrial Disease Modeling: Patients’ Brain in a Dish - Povea-Cabello, Suleva; Villanueva-Paz, Marina; Suárez-Rivero, Juan M.; Álvarez-Córdoba, Mónica; Villalón-García, Irene; Talaverón-Rey, Marta; Suárez-Carrillo, Alejandra; Munuera-Cabeza, Manuel; Sánchez-Alcázar, José A. (Frontiers in Genetics, 2021)
Mitochondrial diseases are a heterogeneous group of rare genetic disorders that can be caused by mutations in nuclear (nDNA) or mitochondrial DNA (mtDNA). Mutations in mtDNA are associated to several maternally inherited genetic diseases which main pathological feature is mitochondrial dysfunction. These diseases although frequently multisystemic, mainly affect organs that require large amounts of energy such as the brain and the skeletal muscle. In contrast to the difficulty of obtaining neuronal and muscle cell models, the development of induced pluripotent stem cells (iPSCs) has shed light on the study of mitochondrial diseases. However, it is still a challenge to obtain an appropriate cellular model in order to find new therapeutic options for people suffering from these diseases. In this review, we deepen in the current models for the most studied mt-tRNA mutation-caused mitochondrial diseases, MELAS (Mitochondrial Encephalomyopathy, Lactic Acidosis and Stroke-like episodes) and MERRF (Myoclonic Epilepsy with Ragged-Red Fibers) syndromes, and their therapeutic management. In particular, we will discuss about the development of a novel model for mitochondrial diseases research, that consists of induced neurons (iNs) generated by direct reprogramming of fibroblasts derived from patients suffering from MERRF syndrome. We hypothesize that iNs will be helpful for mitochondrial diseases modeling since they could mimic patient’s neurons pathophysiology and give us the opportunity to correct the alterations in one of the most affected cellular types in these disorders.